Entrepreneurship and livelihood restoration at Sindh Pakistan: mediating role of firm performance - Kazi, Abdul Ghafoor; Md Yusoff, Rosman; Ismail, Fadillah; Munastiwi, Erni; Arisar, Muzammil Muhammad Khan (American Scientific Publishers, 2017)
Natural Disasters are real phenomenon that occurs in one or another part of the world throughout the year. Disasters affected counties suffer losses such as loss of economy and infrastructures; whilst affected people lose their lives, health, wealth, shelter, education; people become displaced and lose means to earn livelihood. The affected societies become vulnerable to suffer tension and depression, which may lead society to inhuman actives. In order to restore livelihood in such situation, most of the studies are done in developed countries, less are done in developing countries in this perspective. This study determines the relationship in between entrepreneurship and livelihood through firm performance. A research framework was designed to observe such relationship. The population parameters were set and a sample of 446 entrepreneurs was selected from disaster affected districts of Sindh Province at Pakistan using multistage sampling. Self-Administrated Questionnaires was used to collect entrepreneurs’ responses. Prior to final data analysis, data was screened out to eradicate/transform the outliers and missing values; furthermore, the testes were performed to check normality, linearity, Homoscedasticity, and Multicollinearity in data. Final data was analyzed using Hierarchical Multiple Regression Analysis in stepwise manner as suggested Baron and Kenny. Data analysis revealed that entrepreneurship has positive relationship with livelihood restoration and firm performance partially mediated this relationship. Therefore, it concludes that disaster affected society may recover and restores their livelihood promoting entrepreneurship and improving firm performance.